Preliminary construction of reservoir water level control / Muhammad lkmal Ariff Azmee - Azmee, Muhammad lkmal Ariff (Universiti Teknologi MARA, Perak, 2012)
This report briefly describes the processes and methods involved in the preliminary construction of a reservoir water level control. It was developed based on the experience of a five-month detention at a construction site. This report is divided into several parts and started with the title report, objectives, company background and construction project background. The title of this report is the preliminary construction of water reservoir level control and the objective is to identify the preliminary construction methods for reservoir level control. The company background will explain some things about the company where the practical training of students placed. It will start with an introduction followed by objectives, information on companies and managers, organizational charts and concluded with a list of completed projects and undergoing projects. The construction project background will be discussed and explained in detail that describes the selected topic and all the resources only available from the project site. All information obtained from observations, questions and actions that have been made for five months. It is placed in Chapter 3 for attention.